Comparative Analysis of Random Forest and LSTM Models for Customer Churn Prediction Based on Customer Satisfaction and Retention - Gegeleso, Babajide; Ebiesuwa, Oluwaseun (yocto brain, 2025)
Forecasting of Customer churn and prediction is important for sustaining long-term customer relationships and enhancing profitability in competitive markets. This study outlines the comparison of the performance of Random Forest (RF) and Long Short-Term Memory (LSTM) models in predicting customer churn using a dataset of 2,850 customers. The dataset comprises of behavioral, transactional, and satisfaction metrics. Key evaluation metrics include accuracy, precision, recall, F1-score, and AUC-ROC. The result clearly shows that while Random Forest offers strong baseline performance with interpretable results, LSTM captures temporal patterns very effectively and performs better in identifying subtle churn indicators, especially in sequential customer satisfaction data. The result of metrics evaluated shows LSTM has an Accuracy of 88.6%,Precision of 85.3%,Recall of 82.5%,F1-score of 83.9% and AUC-ROC of 0.92 while Random Forest has Accuracy of 85.2%,Precision of 81.5%,Recall of 77.0%,F1- Score of 79.2% and AUC-ROC of 0.89. This shows the preference of LSTM for rapidly changing and large volume dataset over RF excellence in less complicated and sparse dataset